THEORETICAL BASES OF FORMATION OF PROFESSIONAL COMPETENCE OF FUTURE TEACHERS - T. Sabirxodjaeva (International Engineering Journal For Research & Development, 2021)
This article discusses in detail the theoretical foundations of the formation of professional competence of future teachers The young people who are realizing the goals set by our society are the current students.